PENGEMBANGAN E-MODUL BERBASIS LITERASI SAINS PADA MATERI RADIASI ELEKTROMAGNETIK - Nana Nurjannati; M. Rahmad '; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to produce e-module based science literacy that is feasible to use. The subject of this research is e-module based science literacy on electromagnetic radiation lesson. This research used Research and Development method with type 4D. Stages of developing this e-module based science literacy include Define, Design, Develop, and Disseminate. The instrument used is the Science Literacy Validation Scoring Sheets. The validation results of e-module based science literacy on electromagnetic radiation lesson from all aspects have a percentage 86.96% with very decent category. Thus, e-module of physics learning based on science literacy is feasible to be used as a supporting teaching material, as well as basic teaching materials on electromagnetic radiation lesson for grade XII of Senior High School students.Keywords: E-module, Science Literacy, Electromagnetic Radiation